Patients with aldolase B deficiency are characterized by increased intrahepatic triglyceride content - Simons, N; Debray, FG; Schaper, NC; Kooi, ME; Feskens, EJM; Hollak, CEM; Lindeboom, L; Koek, GH; Bons, JAP; Lefeber, DJ; Hodson, L; Schalkwijk, CG; et al. (Oxford University Press, 2019)
CONTEXT:There is an ongoing debate about whether and how fructose is involved in the pathogenesis of nonalcoholic fatty liver disease (NAFLD). A recent experimental study showed an increased intrahepatic triglyceride (IHTG) content in mice deficient for aldolase B (aldo B-/-), the enzyme that converts fructose-1-phosphate to triose phosphates. OBJECTIVE:To translate these experimental findings to the human situation. DESIGN:Case-control study. SETTING:Outpatient clinic for inborn errors of metabolism. PATIENTS OR OTHER PARTICIPANTS:Patients with hereditary fructose intolerance, a rare inborn error of metabolism caused by a defect in aldolase B (n = 15), and healthy persons matched for age, sex, and body mass index (BMI) (n =15). MAIN OUTCOME MEASURE:IHTG content, assessed by proton magnetic resonance spectroscopy. RESULTS:IHTG content was higher in aldo B-/- patients than controls (2.5% vs 0.6%; P = 0.001) on a background of lean body mass (median BMI, 20.4 and 21.8 kg/m2, respectively). Glucose excursions during an oral glucose load were higher in aldo B-/- patients (P = 0.043). Hypoglycosylated transferrin, a surrogate marker for hepatic fructose-1-phosphate concentrations, was more abundant in aldo B-/- patients than in controls (P < 0.001). Finally, plasma β-hydroxybutyrate, a biomarker of hepatic β-oxidation, was lower in aldo B-/- patients than controls (P = 0.009). CONCLUSIONS:This study extends previous experimental findings by demonstrating that aldolase B deficiency also results in IHTG accumulation in humans. It suggests that the accumulation of fructose-1-phosphate and impairment of β-oxidation are involved in the pathogenesis.